High efficiency of ROS production by glycerophosphate dehydrogenase in mammalian mitochondria - Mráček, Tomáš; Pecinová, Alena; Vrbacký, Marek; Drahota, Zdeněk; Houstek, Josef (Archives of biochemistry and biophysics, 2009)
We investigated hydrogen peroxide production in mitochondria with low (liver, heart, brain) and high (brown adipose tissue, BAT) content of glycerophosphate dehydrogenase (mGPDH). ROS production at state 4 due to electron backflow from mGPDH was low, but after inhibition of electron transport with antimycin A high rates of mGPDH-dependent ROS production were observed in liver, heart and brain mitochondria. When this ROS production was related to activity of mGPDH, many-fold higher ROS production was found in contrast to succinate- (39-, 28-, 3-fold) or pyruvate plus malate-dependent ROS production (32-, 96-, 5-fold). This specific rate of mGPDH-dependent ROS production was also exceedingly higher (28-, 66-, 22-fold) compared to that in BAT. mGPDH-dependent ROS production was localized to the dehydrogenase+CoQ and complex III, the latter being the highest in all mitochondria but BAT. Our results demonstrate high efficiency of mGPDH-dependent ROS production in mammalian mitochondria with a low content of mGPDH and suggest its endogenous inhibition in BAT.
Keywords: reaktivní formy kyslíku; potkani Wistar; Pyruvic Acid; Financing, Organized; kyselina jantarová; Electron Transport Complex III; Mitochondria; Rats, Wistar; Cricetinae; Mitochondria, Heart; financování organizované; křečci praví; mozek; Rats; zvířata; Animals; antimycin A; Male; mitochondrie; Glycerolphosphate Dehydrogenase; peroxid vodíku; mužské pohlaví; jaterní mitochondrie; Mitochondria, Liver; techniky in vitro; glycerolfosfátdehydrogenasa; Antimycin A; Electron Transport; Reactive Oxygen Species; transport elektronů; Succinic Acid; srdeční mitochondrie; kyselina pyrohroznová; respirační komplex III; hnědá tuková tkáň; Brain; Hydrogen Peroxide; In Vitro Techniques; krysa rodu Rattus; Adipose Tissue, Brown